Challenges of Non-Soviet Poetry in Minsk During the BSSR Period - Trestman Gershon; Schumann Andrew (Studia Humana, 2025)
The interview given by Gershon Trestman (born July 29, 1947, Minsk), a Russian-language Belarusian and Israeli poet, prose writer, publicist, and playwright. He is a member of the Union of Writers of Israel, the Commonwealth of Russian-Speaking Writers of Israel “Stolitsa,” and the International Federation of Russian Writers. His work has been recognized with the Yu. Stern and Yu. Nagibin awards, as well as a gold medal for “outstanding achievements in literature and the arts” from the California Academy of Sciences. Selected works: The One Who Crossed the River (Tel Aviv, 1996); Golem, or Faust’s Curse (Moscow, 2007); A Small Country with a Great History (Israel, 2008, foreword by Avigdor Lieberman); The Great History of a Small Country (Israel, 2011); The Scroll of Esther (Jerusalem, 2013); The Land of Olive Guardians (Jerusalem, 2013); The Israeli Knot: The History of the Country – The History of Confrontation (Book-Sefer, 2014); The Land of Olive Guardians (Jerusalem, KKL-JNF, 2014); Job (Minsk, New Wineskins, 2014); ... Where There Are No Coordinates. Poems and Epics (Jerusalem, 2017); The Book of Non-Being (Minsk, Logvinov, 2019); Alphabet for Elderly Children (Jerusalem, 2023).